European bat lyssaviruses: an emerging zoonosis. - Fooks, A. R. (Cambridge University Press, 2003)
In Europe, two bat lyssaviruses referred to as European bat lyssaviruses (EBLVs) types 1 and 2 (genotypes 5 and 6 respectively) which are closely related to classical rabies virus are responsible for an emerging zoonosis. EBLVs are host restricted to bats, and have been known to infect not only their primary hosts but also in rare circumstances, induce spillover infections to terrestrial mammals including domestic livestock, wildlife and man. Although spillover infections have occurred, there has been no evidence that the virus adapted to a new host. Since 1977, four human deaths from EBLVs have been reported. None of them had a record of prophylactic rabies immunization. Only fragmentary data exist about the effectiveness of current vaccines in cross-protection against EBLVs. It is clear that EBLV in bats cannot be eliminated using conventional strategies similar to the control programmes based on vaccine baits used for fox rabies in Europe during the 1980s. Due to the protected status of bats in Europe, our knowledge of EBLV prevalence and epidemiology is limited. It is possible that EBLV is under-reported and that the recorded cases of EBLV represent only a small proportion of the actual number of infected bats. For this reason, any interaction between man and bats in Europe must be considered as a possible exposure. Human exposure through biting incidents, especially unprovoked attacks, should be treated immediately with rabies post-exposure treatment and the bat, where possible, retained for laboratory analysis. Preventative measures include educating all bat handlers of the risks posed by rabies-infected animals and advising them to be immunized. This review provides a brief history of EBLVs, their distribution in host species and the public health risks.